Taxonomy, the Cinderella of science, hidden by its evolutionary stepsister - Padial, José M.; Riva, Ignacio De La (Zootaxa, 2007)
While taxonomy is being glorified during the Linnaean 300th anniversary (Anonymous 2007; Hopper 2007), we have observed a dangerous trend in phylogenetics: the placement of taxonomic discoveries in the appendices of science. Studies that aim to address biogeographical or evolutionary hypotheses using phylogenetic analyses have been confronted with the problem of how to proceed with the taxonomic discoveries that emerge during the analysis of the information (e. g. when discovering that a taxon that was thought to be monophyletic is instead paraphyletic). Authors of such studies may be forced by the editorial policy of high impact journals, either to ignore their own taxonomic results or to treat them marginally by including them in on-line appendices (e. g. Wiens et al. 2005; Heinicke et al. 2007). These cases are likely to be more and more common because of the increasing use of phylogenetics without classification purposes (Wheeler 2004; Franz 2005), together with the lack of complete taxonomic knowledge for most organisms (Dubois 2003a). This situation can lead to the production of “phantom taxonomies”: those that first appear in online appendices as downloadable documents, in which both the new taxonomy and the authors are difficult to track. This new term bears a strong resemblance to two other: "phantom nomina" as introduced by Vences et al. (1999) and "phantom references" (Dubois 1999). The term "phantom nomina" refers to new nomina “accidentally” published in amateur publications without proper descriptions and vouchers, while "phantom references" point to references that were quoted as "in press" or " in  preparation" but were never published.